THE IMPACT OF INTERNET ACCESS ON HAPPINESS IN INDONESIA - Felisia, Calista; Dariatno Sihaloho, Estro (Faculty of Economics and Business, University of Pasundan, 2025)
This study examines whether internet access increases happiness in Indonesia. Using provincial-level panel data from 2014, 2017, and 2021, a Random Effects model is applied to examine the relationship between internet access and the Happiness Index across 34 provinces. The analysis also includes education, Gini coefficient, unemployment, sanitation, and GDP per capita as additional factors. The findings show that internet access and education have a significant positive effect on happiness, while income inequality significantly reduces it. Although unemployment and sanitation were not statistically significant, they still contribute to the broader context of well-being. These results highlight the importance of expanding internet access and improving educational access as pathways to increasing happiness. The study also supports the Easterlin Paradox in Indonesia, indicating that higher income alone does not necessarily improve life satisfaction.